Effects of the relationship between exchange rates and oil prices in some oil countries for the period from (1999-2020 - بيداء رزاق حسين (مجلة الغري للعلوم الاقتصادية والادارية, 2022)
Explanation of the extent to which the oil countries and Iraq, including them, are affected by this relationship, whether the effect is from the exchange rate towards the oil price or vice versa. Oil will lead to decisive repercussions in the economic indicators of these countries, and the impact of this relationship will be in two directions. Whenever the direction of the relationship is from the exchange rate towards the oil price, this will lead to repercussions on revenues, spending and economic growth in these countries, and whenever the direction of the relationship is from the oil price towards the exchange rate This will lead to effects on exports and imports (balance of payments), purchasing power and inflation in these countries, and we will try in this research to trace these effects in turn